Pengaruh Stres Kerja, Kepuasan Kerja dan Komitmen Organisasi terhadap Turnover Intention di Apotek Mandiri Pekanbaru - Yasilva, Gatricia; Sulistyandari; Setianingsih, Rahayu (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of job stress, job satisfaction and organizational commitment on turnover intention at Mandiri Pharmacy Pekanbaru. This type of research is quantitative research. Data analysis uses the multiple linear regression analysis method with Turnover Intention as the dependent variable and three independent variables: Job Stress, Job Satisfaction and Organizational Commitment. The research sample was 67 respondents. The results of this study state that the work stress variable has a positive and significant effect on turnover intention. Job satisfaction has a negative and significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention.